TATA KELOLA SAMPAH DI KAMPUNG PINANG SEBATANG BARAT KABUPATEN SIAK TAHUN 2020-2021 - Ida Yulia; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The waste problem is one of the problems that often arises in communities, both urban and in rural areas in overcoming this problem, the village of Pinang Sebatang Barat forms Village-Owned Enterprises or commonly abbreviated as BUMDes is a mandate of Law Number 6 of 2014 Article 87 which states that BUMDes are formed on the basis of the spirit of family and mutual cooperation to utilize all economic potential, natural resources and human resources to improve the welfare of rural communities. BUMKam tuah negeri formed a waste transportation unit in order to assist the village government in realizing a clean village that will become a tourist village but in the waste management of BUMKam Tuah Negeri Kampung Pinang Sebatang Barat there are problems such as the governance of BUMKam Tuah Negeri which still does not carry out supervision, transparency, accountability. The problem found in the field is that there is community opposition regarding the accumulation of garbage that the transport car is damaged and without any temporary unit changes. The purpose of the study was to analyze the implementation of waste governance principles by BUMKam Tuah Negeri in Kampung Pinang Sebatang Barat and to determine the constraints of waste management in Kampung Pinang Sebatang Barat in 2020-2021 in Siak Sri Indrapura regency. In this study, using the theory of good governance according to Mardiasmo because of these four principles, namely: The Rule of Law, Democracy, Transparency, and Accountability.This research method uses a qualitative approach in its research, where data sources are obtained using 3 ways, namely observation, interviews and documentation. The results of this study show that by using the theory of good governance accountability implemented by BUMKam tuah negeri is just reporting without a feed back regarding the truth of the data provided, in transparency BUMKam tuah negeri has not opened financial data to the public either by using banners or other media to provide information to the public. In terms of democracy, BUMKam tuah negeri gives freedom to the community to play a role in the progress of BUMKam tuah negeri, especially the waste transportation unit. The rule of law of BUMKam tuah negeri together with the village government has made village regulations that become a reference in running BUMKam tuah negeri. Some of the obstacles that affect the implementation of BUMKam tuah negeri run the implementation of good governance principles, namely capital and human resources. Keywords: Governance, BUMKam, Waste